Associations between sleep architecture, cortisol concentrations, cognitive performance, and quality of life in patients with Addison's disease - Henry, Michelle (Department of Psychology, 2019)
Recent literature in the neurosciences suggests that there are mechanistic relations between sleep disruption and cognitive (particularly memory) deficits, and that varying concentrations of the hormone cortisol may play a particularly important role in mediating those relations. Because patients with Addison’s disease (AD) experience consistent and predictable periods of sub- and supra-physiological cortisol concentrations (due to lifelong glucocorticoid replacement therapy), and because they frequently report disrupted sleep and poor memory, those presenting with that endocrinological disorder form an ideal population to use in studies testing hypotheses about the ways in which (a) disrupted sleep is related to impaired consolidation of previously learned material (and, hence, poor performance on tests assessing memory for that material), and (b) cortisol concentrations may mediate this relationship between sleep and memory. This dissertation presents four studies that, together, tested those hypotheses. Study 1 (n = 60 per group) found that patients with AD self-reported significantly more disturbed sleep and poorer cognition and quality of life compared to matched healthy controls. Importantly, our analyses suggested that disrupted sleep, and not AD per se, accounted most strongly for the reported cognitive impairment. Study 2 (n = 35 per group) found that patients had significantly poorer objectively-measured declarative memory performance compared to matched healthy controls, but that other domains of cognition were relatively unimpaired. Study 3 (n = 10 per group) suggested that matched healthy controls retained significantly more declarative information than patients. Importantly, while controls retained significantly more declarative information when a period of sleep, rather than waking, separated learning from recall, patients derived no such benefit. Study 4 (n = 7 per group) suggested that, relative to matched healthy controls, patients had different patterns of night-time cortisol secretion, accompanied by significantly reduced slow-wave sleep. Together, these four studies suggest that, despite being on replacement medication, patients with AD still experience disrupted sleep and memory deficits. These disruptions and deficits may be related to the failure of replacement regimens to restore a normal circadian rhythm of cortisol secretion. This pattern of results provides support for existing theoretical frameworks which posit that (in AD and other neuroendocrine, neurological, or psychiatric disorders) disrupted sleep is an important biological mechanism that underlies, at least partially, the memory impairments that patients frequently report experiencing. With specific regard to patients with AD, the findings presented here suggest that future initiatives aimed at improving patients’ cognitive performance (and, indeed, their overall quality of life) should prioritise optimizing sleep. More generally, this dissertation advances our understanding of sleep as a critical biological process essential for cognitive well-being.